“The effect of activating electronic management information systems on improving the performance of workers in light of crises and epidemics: Empirical study” - Shoaib , Haneen (The Arab Journal of Administration, 2021)
The study aims to determine the effect of activating the role of electronic information systems to improve the performance of workers in the Saudi Ministry of National Guard. In addition, to know the availability of requirements for the implementation of electronic administrative information systems, and to determine the impact of the application on improving the performance of workers in periods of crises and epidemics. All that, with the aim of improving the administrative processes in the organization, determining the relationship between the uses of electronic administrative information and improving employee performance. Findings: That the requirements for the implementation of electronic administrative information systems, consisting of (organizational elements, system operating programs, physical elements, and human resources) are available at the Ministry of National Guard. Implementation requirements improve employees’ performance by developing their skills in communicating with others. The implementation of electronic management information systems provides employees with a lot of information about the organization and its operational processes. The implementation of electronic management information systems increases competition in workers performance and gives them the skill to solve problems. There is a positive correlation between the implementation of management information systems and improving employee performance. Recommendations: To explore the scientific and practical methods of making decisions through (identifying the problem, collecting data and information about the problem, providing several solutions to the problem, evaluating all solutions, choosing the best solutions, making decisions, and constantly updating the information). To provide protection programs for computers and communication networks to protect them from piracy and viruses.